2006
DOI: 10.1152/jn.00090.2005
|View full text |Cite
|
Sign up to set email alerts
|

Form and Function of on-off Amacrine Cells in the Amphibian Retina

Abstract: Miller, Robert F., Nathan P. Staff, and Toby J. Velte. Form and function of ON-OFF amacrine cells in the amphibian retina. J Neurophysiol 95: 3171-3190, 2006. First published February 15, 2006 doi:10.1152/jn.00090.2005. ON-OFF amacrine cells were studied with whole cell recording techniques and intracellular staining methods using intact retina-eyecup preparations of the tiger salamander (Ambystoma tigrinum) and the mudpuppy (Necturus maculosus). Morphological characterization of these cells included three-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 66 publications
4
15
0
1
Order By: Relevance
“…Although it is possible that these GABAergic inputs to RBCs are mediated by amacrine cells that are activated purely by ON or OFF channels, combinations of ON and OFF inputs cannot be ruled out (Werblin and Dowling, 1969; Dacheux and Raviola, 1995; Bloomfield and Volgyi, 2007). Previous work on amacrine cells that respond to both light increments and decrements has shown that these cells can mediate feedforward inhibition to ganglion cells (Cook and Werblin, 1994; Taylor, 1999) or feedback inhibition onto bipolar cells (Shields and Lukasiewicz, 2003) and possess a similar sensitivity to TTX (Miller and Dacheux, 1976; Werblin, 1977; Cook and Werblin, 1994; Miller et al, 2006; Bloomfield and Volgyi, 2007), as observed here (Figure 3). …”
Section: Discussionsupporting
confidence: 78%
“…Although it is possible that these GABAergic inputs to RBCs are mediated by amacrine cells that are activated purely by ON or OFF channels, combinations of ON and OFF inputs cannot be ruled out (Werblin and Dowling, 1969; Dacheux and Raviola, 1995; Bloomfield and Volgyi, 2007). Previous work on amacrine cells that respond to both light increments and decrements has shown that these cells can mediate feedforward inhibition to ganglion cells (Cook and Werblin, 1994; Taylor, 1999) or feedback inhibition onto bipolar cells (Shields and Lukasiewicz, 2003) and possess a similar sensitivity to TTX (Miller and Dacheux, 1976; Werblin, 1977; Cook and Werblin, 1994; Miller et al, 2006; Bloomfield and Volgyi, 2007), as observed here (Figure 3). …”
Section: Discussionsupporting
confidence: 78%
“…This finding is consistent with previous modeling papers showing that a single-spiking cell could be caused to fire repetitively by increasing the number of sodium channels or I NaṼ Eliasof et al, 1987;Fohlmeister & Miller, 1997b;Miller et al, 2006!. Repetitive-spiking cells had a larger peak I NaV , lower action potential threshold and larger action potentials than single-spiking cells.…”
Section: Discussionsupporting
confidence: 92%
“…However, this possibility is made very unlikely by the size of the spikes of amacrine cells. These spikes are small (~20 mV), even in intracellular recordings (Barnes and Werblin, 1986, Sakai et al, 1997, Miller et al, 2006). If the amacrine cell’s spike is 5 times smaller than that of the ganglion cell, then it often will not exceed our spike threshold in the pre-processing step.…”
Section: Methodsmentioning
confidence: 97%